Discipline in English Classrooms: intervention strategies in the context of organizational forms - Bečková, Barbora (Univerzita Pardubice, 2014)
This master thesis deals with the issue of discipline in English classrooms. It is divided into the theoretical and practical part. The main aim of the theoretical part is to introduce the essential concepts such as discipline, types of uncooperative behaviour of pupils, intervention strategies and organizational forms. The practical part introduces the multiple-case study which was carried out at one selected basic school. Three teachers of the English language were involved in the study.
Kázeň v hodinách anglického jazyka: intervenční strategie v kontextu organizačních forem vyučování
Keywords: discipline; non-disruptive off-task behaviour; disruptive off-task behaviour; intervention strategies; organizational forms; English language teaching; kázeň; nerušivé nespolupracující chování; rušivé nespolupracující chování; intervenční strategie; organizační formy výuky; výuka anglického jazyka